Preparation method and application of nano flower-shaped bismuth tungstate and copper oxide composite photocatalytic material
Through the preparation of nanoflower-like bismuth tungstate and copper oxide composite materials, a heterojunction structure is formed, which solves the problems of insufficient absorption efficiency of bismuth tungstate photocatalyst under visible light and high electron hole recombination rate, and achieves efficient formaldehyde Degradation effect.
Patent Information
- Application Number
- CN202411361367.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing bismuth tungstate photocatalyst has poor absorption efficiency under visible light, and the photogenerated electron hole recombination rate is high, which limits its photocatalytic activity.
The nanoflower-like bismuth tungstate and copper oxide composite is prepared through hydrothermal reaction and calcination steps to form a heterojunction structure, increase the specific surface area and reaction sites, and promote the separation of photogenerated charges.
It improves photocatalytic activity and formaldehyde degradation rate, is simple to operate and low cost, and is suitable for the degradation of indoor gaseous formaldehyde.
Smart Images

Figure CN119215921A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalyst preparation, and specifically relates to a preparation method and application of a nano flower-shaped bismuth tungstate copper oxide composite photocatalytic material. Background Art
[0002] Formaldehyde is a common VOCs, commonly used in the production process of adhesives, paints, furniture, building materials, home appliances and other products. It is easy to volatilize into indoor air. Long-term exposure to high concentrations of formaldehyde may cause harm to human health, such as respiratory problems, eye irritation and potential carcinogenic risks. Therefore, the development of a gaseous formaldehyde degradation technology that is simple to operate and has no secondary pollution has broad prospects and a certain application market.
[0003] Among the methods for purifying gaseous formaldehyde, there are physical or chemical adsorption, thermal catalytic oxidation, plasma technology and photocatalytic technology. Among them, physical and chemical adsorption are difficult to analyze under the condition that indoor furniture materials slowly release formaldehyde. After a period of time, adsorption equilibrium will be reached, so they are not suitable for the degradation of formaldehyde in indoor environments. Thermal catalytic oxidation and plasma technology are also not suitable for indoor environments due to their use conditions. Photocatalytic oxidation can react at room temperature, and the oxidation products are carbon dioxide and water, which are non-toxic and harmless, and can degrade pollutants at a low concentration level, which is very suitable for indoor formaldehyde degradation.
[0004] Since Akira Fujishima and Honda first discovered the photocatalytic effect of TiO2 in 1972, various photocatalytic properties of TiO2 have become a hot research topic. As one of the most representative semiconductor photocatalytic materials, it has the advantages of being non-toxic, chemically stable, low-cost, and having high photocatalytic and photoelectric properties.
[0005] However, TiO2 has a wide band gap (3.2 eV) and responds only under ultraviolet light, which limits its full utilization of sunlight. Therefore, in recent years, the research on photocatalysts under visible light conditions has gradually attracted attention. Bismuth-based semiconductor materials have become a popular material for a new type of visible light-responsive semiconductor due to their special electronic configuration, appropriate band gap width and controllable surface structure. The conduction band (CB) of Bi2WO6 is composed of W 5d orbitals, and the valence band (VB) is composed of O 2p and Bi 6p orbital hybridization. The hybridization between orbitals leads to the generation of a large number of dispersed valence bands, which promotes the migration of photogenerated holes in the valence band and ultimately enhances the photocatalytic performance of Bi2WO6. The band gap width is about 2.7 eV, which is a type of photocatalyst with a narrow band gap width, so it performs well in the visible light region. In addition to its photocatalytic performance, Bi2WO6 also has other ideal chemical and physical properties, including non-toxicity, good photoelectric stability and ferroelectric piezoelectricity. At the same time, the surface of Bi2WO6 carries a large amount of hydrogen ions, which can increase the transfer efficiency of photogenerated electrons, holes and free radicals, thereby effectively increasing the adsorption and degradation efficiency of pollutants.
[0006] Bi2WO6 has been recognized as a new type of photocatalyst with narrow bandgap and visible light response, which can absorb the energy of visible light to degrade organic pollutants. Despite this, Bi2WO6 material itself still has many shortcomings: (1) Although it can absorb visible light, due to the limitation of band gap, the absorption efficiency of visible light with wavelength greater than 450nm is extremely poor; (2) It is difficult to reduce the recombination rate of photogenerated electrons and holes; (3) The insufficient surface exposed reaction sites limit the adsorption and activation of reactants. Therefore, domestic and foreign researchers have been continuously studying and exploring methods to modify Bi2WO6 photocatalysts, hoping to improve the photocatalytic activity of Bi2WO6 materials, and have also made great progress. From a microscopic point of view, the main ways and principles of modifying Bi2WO6 photocatalysts are: (1) broadening the spectral response range of the material through band regulation measures; (2) promoting the migration and separation of electrons and holes in the material by compounding other semiconductors to form a heterojunction structure; (3) enhancing the adsorption and catalytic performance of the material by increasing the highly active exposed surface and promoting the separation of photoinduced carriers. Summary of the invention
[0007] In view of the problems that the existing bismuth tungstate photocatalyst has poor visible light absorption performance and high photogenerated electron-hole recombination rate, the purpose of the present invention is to provide a preparation method and application of a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material; the preparation method of the present invention is simple and easy to operate. The prepared photocatalyst has a unique nano-flower-like morphology, a large specific surface area and good adsorption, forms a heterojunction with copper oxide, promotes the separation of photogenerated charges, and has good photocatalytic activity.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material, comprising the following steps:
[0010] (1) dissolving a soluble tungstate in water to obtain a solution A; dissolving a soluble bismuth salt in a mixed solvent of water and acetic acid to obtain a solution B; dropping the solution A into the solution B under stirring, stirring and mixing, to obtain a precursor solution;
[0011] (2) subjecting the precursor solution to a hydrothermal reaction, separating the solid by centrifugation after the reaction, washing, drying, and grinding to obtain nano-flower-shaped bismuth tungstate;
[0012] (3) adding nano-flower-shaped bismuth tungstate to a mixed solvent of ethanol and water, adding a soluble copper salt under stirring, stirring, and ultrasonication; under stirring, adjusting the pH of the solution, allowing it to stand for a hydrothermal reaction, and after the reaction is completed, centrifuging to separate the solid, washing, drying, and grinding to obtain a bismuth tungstate copper oxide composite powder;
[0013] (4) The bismuth tungstate copper oxide composite powder is heated to 350-450° C. and calcined for 3 h-5 h, and then cooled to room temperature to obtain a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material.
[0014] Furthermore, in step (1), the soluble tungstate is Na2WO4·2H2O; the soluble bismuth salt is Bi(NO3)3·5H2O;
[0015] Furthermore, in step (1), the volume ratio of water to acetic acid in the mixed solvent of water and acetic acid is 4:1 to 3:1;
[0016] Furthermore, in step (1), the concentration of the soluble tungstate in the solution A is 0.02 mol / L to 0.03 mol / L; and the concentration of the soluble bismuth salt in the solution B is 0.04 mol / L to 0.06 mol / L.
[0017] Furthermore, in step (1), the molar ratio of the W element in solution A to the Bi element in solution B is 1:6 to 1:5.
[0018] Furthermore, in step (2), the temperature of the hydrothermal reaction is 180°C to 200°C, and the time is 2-4h;
[0019] Furthermore, in step (2), the washing is performed using anhydrous ethanol and deionized water.
[0020] Furthermore, in step (3), the volume ratio of ethanol to water in the mixed solvent of ethanol and water is 1:1 to 1.5;
[0021] Furthermore, in step (3), the concentration of the nano-flower-shaped bismuth tungstate in the mixed solvent of ethanol and water is 2 g / L to 2.5 g / L;
[0022] Further, in step (3), the soluble copper salt is Cu(CO2CH3)2·H2O;
[0023] Furthermore, in step (3), the stirring time is 30 min to 45 min;
[0024] Furthermore, in step (3), the ultrasonication time is 15 min to 30 min;
[0025] Furthermore, in step (3), Na2CO3 powder is added to adjust the pH of the solution;
[0026] Furthermore, in step (3), the standing time is 2h to 3h;
[0027] Furthermore, in step (3), the washing is performed with anhydrous ethanol and deionized water;
[0028] Furthermore, in step (3), the temperature of the hydrothermal reaction is 80° C. to 100° C., and the time is 10 to 12 hours.
[0029] Furthermore, in step (3), the mass ratio of the soluble copper salt added in terms of CuO to the nano-flower-shaped bismuth tungstate is 5% to 30%;
[0030] Preferably, in step (3), the mass ratio of the soluble copper salt added in terms of CuO to the nano-flower-shaped bismuth tungstate is 10% to 15%;
[0031] Furthermore, in step (3), the pH of the solution is adjusted to 10-11.
[0032] Furthermore, in step (4), the heating rate is 2 to 5°C / min.
[0033] The invention provides a nano flower-shaped bismuth tungstate copper oxide composite photocatalytic material, which is prepared by the above-mentioned preparation method.
[0034] The present invention provides an application of the nano flower-shaped bismuth tungstate copper oxide composite photocatalytic material in photocatalytic degradation of gas formaldehyde.
[0035] Compared with the prior art, the present invention has the following advantages:
[0036] 1. The bismuth tungstate prepared by the present invention has a unique nano-flower-like morphology, which increases its specific surface area, has good adsorption of formaldehyde, and enhances the photocatalytic reaction sites.
[0037] 2. The present invention enables bismuth tungstate and copper oxide to form a heterojunction, which promotes the separation efficiency of photogenerated charges, has good photocatalytic activity, and has a high degradation rate for formaldehyde.
[0038] 3. The present invention is simple to operate and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 XRD diagrams of the nano-flower-shaped bismuth tungstate-copper oxide composite photocatalytic materials prepared in Examples 1-4 and the nano-flower-shaped bismuth tungstate and copper oxide in Comparative Example 1.
[0040] Figure 2 This is a SEM image of the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material prepared in Example 1-4.
[0041] Figure 3 This is the SEM image of the nano-flower-shaped bismuth tungstate prepared in Comparative Example 1.
[0042] Figure 4 The UV-visible light absorption spectra of the photocatalysts of Examples 1-4 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0043] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0044] Example 1
[0045] A method for preparing a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material comprises the following steps:
[0046] (1) 0.08 g Na2WO4·2H2O was dissolved in 10 mL deionized water, which was solution A. 0.72 g Bi(NO3)3·5H2O was stirred and dissolved in 30 mL of a mixed solvent of deionized water and acetic acid in a volume ratio of 4:1, which was solution B. The molar ratio of Na2WO4·2H2O to Bi(NO3)3·5H2O was 1:6. Solution A was slowly dripped into solution B under stirring, and the mixture was fully stirred to obtain a precursor solution.
[0047] (2) placing the precursor solution in a reactor for a hydrothermal reaction at a temperature of 180° C. for 3 h; after the reaction, the solid is separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain nano-flower-shaped bismuth tungstate.
[0048] (3) 0.1 g of nano-flower-shaped bismuth tungstate was added to a mixed solvent of 20 mL of anhydrous ethanol and 20 mL of deionized water, and 0.016 g of Cu(CO2CH3)2·H2O was added under stirring. The mixture was stirred for 30 min and ultrasonicated for 10 min. Then, Na2CO3 powder was added while stirring to adjust the pH of the solution to 10. After standing for 2 h, the solution was placed in a reactor for hydrothermal reaction at a temperature of 80°C for 12 h. After the reaction, the solid was separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain a bismuth tungstate copper oxide composite powder.
[0049] (4) The bismuth tungstate copper oxide composite powder was heated to 350°C in a muffle furnace and calcined for 3 h (heating rate of 2°C / min), and then cooled to room temperature to obtain a product called BWC-1.
[0050] Example 2
[0051] A method for preparing a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material comprises the following steps:
[0052] (1) 0.08 g Na2WO4·2H2O was dissolved in 10 mL deionized water, which was solution A. 0.72 g Bi(NO3)3·5H2O was stirred and dissolved in 30 mL of a mixed solvent of deionized water and acetic acid in a volume ratio of 4:1, which was solution B. The molar ratio of Na2WO4·2H2O to Bi(NO3)3·5H2O was 1:6. Under stirring, solution A was slowly dripped into solution B, and the mixture was fully stirred to obtain a precursor solution.
[0053] (2) placing the precursor solution in a reactor for a hydrothermal reaction at a temperature of 180° C. for 3 h; after the reaction, the solid is separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain nano-flower-shaped bismuth tungstate.
[0054] (3) 0.1 g of nano-flower-shaped bismuth tungstate was added to a mixed solvent of 20 mL of anhydrous ethanol and 20 mL of deionized water, and 0.031 g of Cu(CO2CH3)2·H2O was added under stirring. The mixture was stirred for 30 min and ultrasonicated for 10 min. Then, Na2CO3 powder was added while stirring to adjust the pH of the solution to 10. After standing for 2 h, the solution was placed in a reactor for hydrothermal reaction at a temperature of 80°C for 12 h. After the reaction, the solid was separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain a bismuth tungstate copper oxide composite powder.
[0055] (4) The bismuth tungstate copper oxide composite powder was heated to 350°C in a muffle furnace and calcined for 3 h (heating rate of 2°C / min), and then cooled to room temperature to obtain a product called BWC-2.
[0056] Example 3
[0057] A method for preparing a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material comprises the following steps:
[0058] (1) 0.08 g Na2WO4·2H2O was dissolved in 10 mL deionized water, which was solution A. 0.72 g Bi(NO3)3·5H2O was stirred and dissolved in 30 mL of a mixed solvent of deionized water and acetic acid in a volume ratio of 4:1, which was solution B. The molar ratio of Na2WO4·2H2O to Bi(NO3)3·5H2O was 1:6. Under stirring, solution A was slowly dripped into solution B, and the mixture was fully stirred to obtain a precursor solution.
[0059] (2) placing the precursor solution in a reactor for a hydrothermal reaction at a temperature of 180° C. for 3 h; after the reaction, the solid is separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain nano-flower-shaped bismuth tungstate.
[0060] (3) 0.1 g of nano-flower-shaped bismuth tungstate was added to a mixed solvent of 20 mL of anhydrous ethanol and 20 mL of deionized water, and 0.058 g of Cu(CO2CH3)2·H2O was added under stirring. The mixture was stirred for 30 min and ultrasonicated for 10 min. Then, Na2CO3 powder was added while stirring to adjust the pH of the solution to 10. After standing for 2 h, the solution was placed in a reactor for hydrothermal reaction at a temperature of 80°C for 12 h. After the reaction, the solid was separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain a bismuth tungstate copper oxide composite powder.
[0061] (4) The bismuth tungstate copper oxide composite powder was heated to 350°C in a muffle furnace and calcined for 3 h (heating rate of 2°C / min), and then cooled to room temperature to obtain a product called BWC-3.
[0062] Example 4
[0063] A method for preparing a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material comprises the following steps:
[0064] (1) 0.08 g Na2WO4·2H2O was dissolved in 10 mL deionized water, which was solution A. 0.72 g Bi(NO3)3·5H2O was stirred and dissolved in 30 mL of a mixed solvent of deionized water and acetic acid in a volume ratio of 4:1, which was solution B. The molar ratio of Na2WO4·2H2O to Bi(NO3)3·5H2O was 1:6. Under stirring, solution A was slowly dripped into solution B, and the mixture was fully stirred to obtain a precursor solution.
[0065] (2) placing the precursor solution in a reactor for a hydrothermal reaction at a temperature of 180° C. for 3 h; after the reaction, the solid is separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain nano-flower-shaped bismuth tungstate.
[0066] (3) 0.1 g of nano-flower-shaped bismuth tungstate was added to a mixed solvent of 20 mL of anhydrous ethanol and 20 mL of deionized water, and 0.075 g of Cu(CO2CH3)2·H2O was added under stirring. The mixture was stirred for 30 min and ultrasonicated for 10 min. Then, Na2CO3 powder was added while stirring to adjust the pH of the solution to 10. After standing for 2 h, the solution was placed in a reactor for hydrothermal reaction at a temperature of 80°C for 12 h. After the reaction, the solid was separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain a bismuth tungstate copper oxide composite powder.
[0067] (4) The bismuth tungstate copper oxide composite powder was heated to 350°C in a muffle furnace and calcined for 3 h (heating rate of 2°C / min), and then cooled to room temperature to obtain a product called BWC-4.
[0068] Comparative Example 1
[0069] A method for preparing a nano-flower-shaped bismuth tungstate photocatalytic material comprises the following steps:
[0070] (1) 0.08 g Na2WO4·2H2O was dissolved in 10 mL deionized water, which was solution A. 0.72 g Bi(NO3)3·5H2O was stirred and dissolved in 30 mL of a mixed solvent of deionized water and acetic acid in a volume ratio of 4:1, which was solution B. The molar ratio of Na2WO4·2H2O to Bi(NO3)3·5H2O was 1:6. Solution A was slowly dripped into solution B under stirring, and the mixture was fully stirred to obtain a precursor solution.
[0071] (2) placing the precursor solution in a reactor for a hydrothermal reaction at a temperature of 180° C. for 3 h; after the reaction, the solid is separated by centrifugation, washed three times with anhydrous ethanol and deionized water respectively, dried, and ground to obtain a nanoflower-like bismuth tungstate photocatalytic material, referred to as BW.
[0072] Comparative Example 2
[0073] A method for preparing a copper oxide material comprises the following steps:
[0074] 0.1 g Cu(CO2CH3)2·H2O was added to a mixed solvent of 20 mL anhydrous ethanol and 20 mL deionized water, stirred for 30 min, and ultrasonicated for 10 min. Then, 0.04 g Na2CO3 powder was added while stirring to adjust the pH of the solution to 10. After standing for 2 h, the solution was placed in a reactor for hydrothermal reaction at a temperature of 80°C for 12 h. After the reaction, the solid was separated by centrifugation, washed 3 times with anhydrous ethanol and deionized water respectively, dried, ground, heated to 350°C in a muffle furnace, calcined for 3 h (heating rate of 2°C / min), and cooled to room temperature to obtain CuO.
[0075] 1. X-ray diffraction (XRD) test
[0076] The composition and crystal structure of the samples were tested using a Cu target Kα radiation source on a Bruker D8 Advance. The test results are shown in Figure 1 .
[0077] from Figure 1 It can be seen that the composite materials BWC1-4 and BW have characteristic peaks at 28°, 32°, 47°, and 55°, which are attributed to the (131), (200), (202), and (133) crystal planes of Bi2WO6 (JCPDS standard card 39-0256). Among them, 32° coincides with the (110) crystal plane of CuO (JCPDS standard card 89-5896), and the peak value becomes larger. In addition, the BWC-4 composite material has a higher CuO content, and characteristic peaks appear at 35° and 38°, which belong to the (002) and (111) crystal planes of CuO, confirming that the materials are successfully composited.
[0078] 2. Scanning electron microscopy (SEM) test
[0079] A scanning electron microscope (SU8220) was used to observe the microstructure of the samples. Figure 2 and Figure 3 , Figure 2 The four groups of pictures from top to bottom are BWC1-4, Figure 3 For BW.
[0080] Depend on Figure 3 It can be seen that the nanoflower-like bismuth tungstate photocatalytic material BW has a nanoflower-like structure composed of nanosheets and has a high specific surface area. Figure 2 It can be seen that the nanoflower-like bismuth tungstate copper oxide composite photocatalyst BWC is based on the nanoflower-like bismuth tungstate photocatalyst BW, and copper oxide is attached to the surface of bismuth tungstate nanosheets in the form of diamond nanorods. Among them, BWC-4 appears a scattered single-phase CuO with a special morphology, which is consistent with the XRD results.
[0081] 3. Photocatalytic degradation of formaldehyde performance test
[0082] Nano flower-shaped bismuth tungstate copper oxide composite photocatalytic material is used for gas formaldehyde degradation. The application method is as follows: take 0.15g of nano flower-shaped bismuth tungstate copper oxide composite photocatalytic material and evenly distribute it in a culture dish, put it in a Tedlar air bag, inject 3μL of formaldehyde solution, fill it with 4L of fresh air, and put the air bag in a 60℃ oven and heat it for 20min to completely gasify it. The entire degradation process is first dark adsorbed for 1.5h under light-proof conditions, and a xenon lamp equipped with a 420nm cutoff filter is used for photocatalytic reaction. Every 30min, 5mL of gas in the air bag is absorbed, and the formaldehyde concentration is detected using phenol reagent spectrophotometry. The formaldehyde removal rate is calculated according to the following formula, and the formaldehyde degradation performance of the reaction catalyst material is calculated.
[0083] Removal efficiency (%) = (C0-C) / C0×100%
[0084] Wherein, C0 is the concentration of gaseous pollutants when adsorption equilibrium is reached, in ppm; C is the concentration of gaseous pollutants at each sampling, in ppm. The test results are shown in Table 1.
[0085] As can be seen from Table 1, formaldehyde is hardly degraded under blank conditions and under conditions with only copper oxide. The formaldehyde degradation rate of BW nanoflower-like bismuth tungstate photocatalyst after 5 hours of illumination is only 28%. After being compounded with copper oxide, the formaldehyde degradation rate is greatly improved, among which BWC-2 has the best effect, reaching 89%. BWC-3 may have too much surface nano-copper oxide attached, which affects the adsorption of formaldehyde molecules on the surface of bismuth tungstate nanosheets, resulting in a decrease in its formaldehyde degradation rate compared with BWC-2 and BWC-4.
[0086] Table 1
[0087]
[0088]
[0089] 4. UV-vis diffuse reflectance spectra (UV-vis DRS) test
[0090] UV-visible diffuse reflectance spectroscopy measures the absorption capacity of the catalyst to light of different wavelengths in the UV-visible range, and calculates its bandgap width. Hitachi U-3900 spectrophotometer was used to perform UV-vis diffuse reflectance spectroscopy to characterize the ability of the sample to absorb ultraviolet and visible light (with BaSO4 as the reflection standard). The test results are shown in Figure 4 .
[0091] Depend on Figure 4 It can be seen that compared with the nano-flower-like bismuth tungstate photocatalyst BW, the nano-flower-like bismuth tungstate copper oxide composite photocatalyst BWC has a higher absorbance in the overall spectral band, indicating that it has better photocatalytic activity; and the cut-off wavelength is longer, which means that more visible light can be absorbed. The combination of bismuth tungstate and copper oxide broadens the absorption spectrum and increases the utilization rate of visible light. The absorbance of BWC-3 in the ultraviolet band is slightly lower than that of BWC1-2, which may be caused by excessive shielding of the light source by copper oxide on the surface of bismuth tungstate, while BWC-4 forms a single-phase copper oxide, which alleviates this problem. Figure 2 It can be confirmed.
[0092] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the specific implementation methods of the specification of the present invention are described above, it should be clear that the present invention is not limited to the scope of the specific implementation methods. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material, characterized in that: The following steps are involved: (1) Dissolve soluble tungstate in water to obtain solution A; Dissolving a soluble bismuth salt in a mixed solvent of water and acetic acid to obtain a solution B; dropping solution A into solution B under stirring, stirring and mixing, to obtain a precursor solution; (2) subjecting the precursor solution to a hydrothermal reaction, separating the solid by centrifugation after the reaction, washing, drying, and grinding to obtain nano-flower-shaped bismuth tungstate; (3) adding nano-flower-shaped bismuth tungstate to a mixed solvent of ethanol and water, adding soluble copper salt under stirring, stirring, and ultrasonicating; Under stirring, adjusting the pH of the solution, allowing it to stand for hydrothermal reaction, separating the solid by centrifugation, washing, drying, and grinding to obtain bismuth tungstate copper oxide composite powder; (4) The bismuth tungstate copper oxide composite powder is heated to 350° C. to 450° C. and calcined for 3 h to 5 h, and then cooled to room temperature to obtain a nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material.
2. The method for preparing the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material according to claim 1, characterized in that: In step (1), the soluble tungstate is Na2WO4·2H2O; the soluble bismuth salt is Bi(NO3)3·5H2O; In step (1), the volume ratio of water to acetic acid in the mixed solvent of water and acetic acid is 4:1 to 3:1; In step (1), the concentration of the soluble tungstate in the solution A is 0.02 mol / L to 0.03 mol / L; the concentration of the soluble bismuth salt in the solution B is 0.04 mol / L to 0.06 mol / L.
3. The method for preparing the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material according to claim 1, characterized in that: In step (1), the molar ratio of the W element in solution A to the Bi element in solution B is 1:6 to 1:
5.
4. The method for preparing the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material according to claim 1, characterized in that: In step (2), the temperature of the hydrothermal reaction is 180° C. to 200° C., and the time is 2 to 4 hours; In step (2), the washing is performed using anhydrous ethanol and deionized water.
5. The method for preparing the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material according to claim 1, characterized in that: In step (3), The volume ratio of ethanol to water in the mixed solvent of ethanol and water is 1:1 to 1.5; The concentration of the nano-flower-shaped bismuth tungstate in the mixed solvent of ethanol and water is 2 g / L to 2.5 g / L; The soluble copper salt is Cu(CO2CH3)2·H2O; The stirring time is 30min to 45min; The ultrasonic time is 10min to 30min; The pH of the solution is adjusted by adding Na2CO3 powder; The standing time is 2h to 3h; The washing is performed with anhydrous ethanol and deionized water.
6. The method for preparing the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material according to claim 1, characterized in that: In step (3), the temperature of the hydrothermal reaction is 80°C to 100°C, and the time is 10 to 12 hours.
7. The method for preparing the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material according to claim 1, characterized in that: In step (3), the mass ratio of the soluble copper salt added in terms of CuO to the nano-flower-shaped bismuth tungstate is 10% to 15%; In step (3), the pH of the solution is adjusted to 10-11.
8. The method for preparing the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material according to claim 1, characterized in that: In step (4), the heating rate is 2 to 5°C / min.
9. The nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the nano-flower-shaped bismuth tungstate copper oxide composite photocatalytic material according to claim 9 in photocatalytic degradation of gas formaldehyde.
Citation Information
Patent Citations
Copper / bismuth tungstate composite photocatalytic material and preparation method thereof
CN104607200A
Carbon dioxide reduction composite photocatalytic material, preparation method and application
CN117680176A
Hydrothermal method for preparing nano crystal Bi2WO6 powder photocatalytic material with visible light activity
CN1709567A
